Análise do efeito de inseticidas neonicotinóides sobre a orientação e coleta de alimento de operárias de Apis mellifera L., 1758 (Hymenoptera: Apidae) - Nominato, Fellipe Chaves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Apis mellifera bees has its great importance as one of the most economically valuable pollinators for crops worldwide, ensuring cross-pollination and increasing fruit yield. On the other hand, increasingly more agricultural chemicals developed in order to control weeds, fungi and insect pests to ensure productivity. Insecticides are used on a large scale in the state of São Paulo, in citrus crops to control huanglongbing (HLB) and sugar cane for the control various pests. Applications are usually made by aircraft and as a result a significant mortality is observed in apiaries near the plantations. Honey bees can come into contact with such chemical agente through their collection of water activities, plant resins, pollen and néctar. The resulting poisoning of this exposure can be lethal, which is readily detectable or cause effects on the physiology and insect behavior. These effects, which in turn are hardly detectable, can be palsy, disorientation or behavioral changes; but can compromisse the entire social structure of the colony. For this reason the objectives of this project were to study the bee orientation capacity A. mellifera and the effects of thiamethoxam and acetamiprid insecticide via topical application using the experimental model of the maze, which reproduces the foraging activities in the field. It was observed that sublethal doses (LD50/100, LD50/10 and LD50) of thiamethoxam and acetamiprid insecticides, applied topically, have caused deleterious effects in the maze tests. For thiamethoxam, there was an increase in flight times and food collection and worse performance for the three doses in compared to control group. For acetamiprid, there was an increase in flight times and food collection, worse performance and lower amount of food collected for the three doses in compared to control group. The method of analysis of the flight behavior and food collection employee, can be directly related to the activity of bees ...

A abelha Apis mellifera tem sua grande importância por ser um dos polinizadores economicamente mais valiosos para as culturas em todo o mundo, garantindo a polinização cruzada e aumentando a produtividade de frutos. Por outro lado, a agricultura cada vez mais desenvolve produtos químicos a fim de controlar plantas daninhas, fungos e insetos-praga para garantir a produtividade. Os inseticidas são utilizados em grande escala no interior do estado de São Paulo, nas culturas de citrus para o controle do huanglongbing (HLB) e na cana de açúcar para o controle de diversas pragas. As aplicações normalmente são feitas por aviões e como resultado uma mortandade expressiva é observada em apiários próximos das plantações. As abelhas melíferas podem entrar em contato com tal agente químico através de suas atividades de coleta de água, resinas vegetais, pólen e néctar. A intoxicação resultante desta exposição pode ser letal, o que é facilmente detectável, ou causar efeitos na fisiologia e no comportamento do inseto. Esses efeitos, que por sua vez são dificilmente detectáveis, podem ser paralisia, desorientação ou mudanças comportamentais; porém podem comprometer toda a estrutura social da colônia. Por esta razão os objetivos desse projeto foram estudar a capacidade de orientação de abelhas A. mellifera e os efeitos dos inseticidas tiametoxam e acetamiprido via aplicação tópica utilizando o modelo experimental do labirinto, que reproduz as atividades de forrageamento em campo. Observou-se que as doses subletais (DL50/100, DL50/10 e DL50) dos inseticidas tiametoxam e acetamiprido, aplicadas topicamente, causaram efeitos deletérios nos testes de labirinto. Para o tiametoxam, houve aumento nos tempos de vôo e coleta de alimento e pior performance para as três doses em relação ao grupo controle. Para o acetamiprido, houve aumento nos tempos de vôo e coleta de alimento, pior performance e menor quantidade de alimento...
Keywords: Bees; Abelha; Inseticidas; Animais - Comportamento; Toxicologia; Animais - Alimentos